Evaluation of efficacy of skin cleansing with chlorhexidine in prevention of neonatal nosocomial sepsis – a randomized controlled trial. (17th January 2016) - Gupta, Basudev; Vaswani, Narain Das; Sharma, Deepak; Chaudhary, Uma; Lekhwani, Seema
Abstract: Aim : The aim of this study was to evaluate the efficacy of skin cleansing with chlorhexidine (CHD) in the prevention of neonatal nosocomial sepsis – a randomized controlled trial. Methods : This study design was a randomized controlled trial carried out in a tertiary care center of north India. About 140 eligible neonates were randomly allocated to either the subject area group (wiped with CHD solution till day seven of life) or the control group (wiped with lukewarm water). The primary outcome studied was to determine the decrease in the incidence of neonatal nosocomial sepsis (blood culture proven) in the intervention group. Results : Out of 140 enrolled neonates, 70 were allocated to each group. The ratio of positive blood culture among the CHD group was 3.57%, while the ratio of positive blood culture among the control group was 6.85%. There was trending towards a reduction in blood culture proven sepsis in the intervention group, although the remainder was not statistically significant. A similar decreasing trend was observed in rates of skin colonization, duration of hospital stay, and duration of antibiotic treatment. Conclusion : CHD skin cleansing decreases the incidence of blood culture sepsis and could be an easy and cheap intervention for reducing the neonatal sepsis in countries where the neonatal mortality rate is high because of sepsis.